Charitable work in the light of the holy Quran and its sustainable development effects: The direct aid society in Kuwait as a case study / Mohammed Abdo Mohammed Al-Kubati - Mohammed Abdo , Mohammed Al-Kubati (2019)
This study deals with the relationship between charitable work in the light of the Holy Quran and sustainable development, and it has been selected the Direct Aid Society in Kuwait as a case study. This study derives its significance from its first reference, the Holy Quran. This study differs from the previous studies in the theory perspective, that dealing with the sustainable development effects in the light of the Holy Quran and applied it on the Direct Aid Society in Kuwait. This study aims to define the concept of charitable work in the Holy Quran and contemporary Islamic thought, to identify the fields of charitable work in the light of the Holy Quran and contemporary Islamic thought, to demonstrate the differences in sustainable development between the positive perspective and the Quranic perspective, to highlight the sustainable development effects of charitable work in the light of the Holy Quran, to clarify the sustainable development effects of charity work in the Direct Aid Society. This study adopted the inductive method by following the Quran's verses focusing on the charitable work in the Holy Quran. It also adopted the analytical descriptive approach and it has been chosen the interview as a research tool to achieve the above objectives. The study found that charitable work in the light of the Holy Quran is the benefit of others as authorized by Allah for the sake of his satisfaction, and that includes the act of good and calling for good. It also found that the most important differences in the concept of sustainable development between the Qur'anic perspective and the positive perspective are that the Qur'anic perspective takes into account the interests of the world and the Hereafter, and the Qur'anic perspective takes in the account the benefits and damages based on the balance of Islamic law, contrary to the positive perspective that focuses only on the mundane interests determined by human beings themselves. It is found also that charitable work contributes to sustainable development, scientific and operational development, which includes social, economic and environmental development. It has been found that charitable work in the Direct Aid Society is in accordance with the Quranic perspective, and its most important developmental effects contribute to the spread of Islam, reduce ignorance, reduce poverty and disease in the target communities, develop education, develop health care, expanding agricultural projects, and providing clean water to needy.